АССОЦИАЦИЯЛАР ИНДИВИДУАЛЛИГИНИНГ ТАШҚИ ОМИЛЛАРИ (Scientific journal of the Fergana State University, 2023)
The article considers the divisions of the associative reactions into external and internal factors, mainly the peculiarities of the external factors are under discussion. The results of the associative experiments are analyzed.